Plasma pharmacokinetics and tissue depletion of cyromazine and its metabolite melamine following oral administration in laying chickens. Issue 5 (29th November 2016) - Rairat, T.; Ou, S. C.; Chang, S. K.; Li, K. P.; Vickroy, T. W.; Chou, C. C.
Abstract : The study was designed to characterize the plasma pharmacokinetics and tissue depletion profiles (including eggs) of cyromazine (CYR) in chickens following oral administration alone or in combination with melamine (MEL). In order to assess the pharmacokinetic profile of CYR, chickens were administered 1 or 10 mg/kg (single oral doses), whereas residue studies were conducted in chickens fed CYR alone (5 or 10 mg/kg) or CYR (5 mg/kg) and MEL (5 mg/kg) for a period of 14 days. Estimates for the apparent volume of distribution (1.66 L/kg), clearance (7.17 mL/kg/min), and elimination half‐life (2.82 h) were derived by noncompartmental analyses. The highest concentration of CYR occurred in liver but fell below detectable limits within 3 days following drug withdrawal from feed. Combined feeding of MEL with CYR did not significantly alter CYR tissue levels. CYR residues were detected only in egg white and were undetectable at the 2nd day postadministration. No MEL was found in eggs unless it had been added to the feed, and when present, it almost exclusively restricted to the egg white. Based upon the results of this initial study of CYR pharmacokinetics and residue depletion, it appears that use of CYR as a feed additive either alone (5 or 10 mg/kg) or in combination with MEL (both agents at 5 mg/kg) does not produce unsafe residue levels in edible products as long as appropriate withdrawal periods are followed for tissues (3 days) and eggs (2 days). However, our results indicate that adoption of a zero‐day withdrawal period should be reconsidered in light of these results.